PROPAGATION OF COMMUNIST IDEOLOGY THROUGH CULTURAL-EDUCATIONAL INSTITUTIONS DURING THE SOVIET GOVERNMENT (World Bulletin of Social Sciences, 2026)
This article analyzes the activities of cultural-educational institutions during the Soviet era and their ideological functions. It examines how Soviet ideology was instilled among the population through cultural institutions— such as clubs, libraries, cultural centers, auto clubs, and museums—and provides a detailed analysis of the development plans for cultural-educational institutions in the Uzbek SSR, the activities of auto clubs, and the methods used to politically and morally educate young people.